2015
DOI: 10.15171/ijb.1058
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Shikalkin Production in Arnebia euchroma Callus by a Fungal Elicitor, Rhizoctonia solani

Abstract: Background: There is a growing demand for mass production of shikalkin (a natural pigment consisted of shikonin and alkannin) due to its increasing applications in cosmetics, pharmaceutical and nutrition industries. The root of Iranian Arnebia euchroma produces shikalkin. The promising capability of this plant for shikalkin production has already been demonstrated in cell culture studies. Objectives: Elicitation effect of Rhizoctonia solani (R. solani) in comparison with the effects of Cu 2+ , methyl jasmonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Similarly, Paraburkholderia phytofirmans strain PsJN is a well-known plant colonizer that shows hormone and ACC deaminase production and is known to elicit plant responses ( 38 , 39 ). Fungal elicitors, which enhance A/S production, have been previously described for the Boraginaceae species Arnebia euchroma ( 40 , 41 ). In our study we found a moderate positive correlation between the root fungal rASV41 ( Penicillium jensenii ) and higher A/S levels (HPLC, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Paraburkholderia phytofirmans strain PsJN is a well-known plant colonizer that shows hormone and ACC deaminase production and is known to elicit plant responses ( 38 , 39 ). Fungal elicitors, which enhance A/S production, have been previously described for the Boraginaceae species Arnebia euchroma ( 40 , 41 ). In our study we found a moderate positive correlation between the root fungal rASV41 ( Penicillium jensenii ) and higher A/S levels (HPLC, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that different exogenous hormones have various effects on shikonin accumulation. For instance, GA [29] and ABA have significantly negative impacts on shikonin biosynthesis, while MeJA and SA [12,16,30,31]can effectively promote it. In our study, the content of endogenous GA4 in AEHR under 30% NH4 + treatment did not change significantly within 48h, suggesting that GA may not be involved in the regulation process of NH4 + toxicity in AEHR.…”
Section: Hormone Metabolism Of Aehr Under Nh4 + Toxicitymentioning
confidence: 99%
“…They found the addition of exogenous SA caused a decreased activity of PHB geranyltransferase, one of the key regulatory enzymes in shikonin biosynthesis [30]. In another study, Arghavani et al reported higher enhancing effects of SA compared to JA [12]. There is no report on the relationship between the endogenous content of SA and shikonin production.…”
Section: 4shikonin Synthesis Of Aehr Under Nh4+ Toxicity and Its Poss...mentioning
confidence: 99%
See 1 more Smart Citation
“…After that, a medium without NH 4 + was widely used for shikonin production in vitro using cell, tissue, and organ cultures of L. erythrorhizon, A. euchroma, and Onosma paniculatum. To optimize the culture conditions, the effects of various medium compositions, abiotic/biotic elicitors, and signal transduction molecules on shikonin synthesis in callus, cell suspension, and hairy root cultures have been widely studied [9,[11][12][13][14][15][16]. However, the effects of nitrogen on shikonin synthesis remain elusive.…”
Section: Introductionmentioning
confidence: 99%